Funkcja edukacyjna w pielęgniarstwie podstawy do poszukiwania skutecznych rozwiązań logistycznych = Educational function in nursing basics to look for effective logistics solutions - Guz, Ewa Teresa; Nalepa, Dorota; Czekirda, Marta; Brodowicz, Magdalena (Journal of Education, Health and Sport, 2016)
Guz Ewa, Nalepa Dorota, Czekirda Marta, Brodowicz Magdalena. Funkcja edukacyjna w pielęgniarstwie podstawy do poszukiwania skutecznych rozwiązań logistycznych = Educational function in nursing basics to look for effective logistics solutions. Journal of Education, Health and Sport. 2016;6(8):145-153. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59993 http://ojs.ukw.edu.pl/index.php/johs/article/view/3740 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Funkcja edukacyjna w pielęgniarstwie podstawy do poszukiwania skutecznych rozwiązań logistycznych Educational function in nursing basics to look for effective logistics solutions Guz Ewa Katedra i Zakład Pielęgniarstwa Neurologicznego Uniwersytet Medyczny w Lublinie Nalepa Dorota Wojewódzki Szpital Specjalistyczny Oddział Neurologii Uniwersytet Medyczny w Lublinie Czekirda Marta Zakład Podstaw Pielęgniarstwa i Dydaktyki Medycznej Uniwersytet Medyczny w Lublinie Brodowicz Magdalena Katedra i Zakład Pielęgniarstwa Pediatrycznego Uniwersytet Medyczny w Lublinie Guz Ewa Katedra i Zakład Pielęgniarstwa Neurologicznego 20-954 Lublin ul. K. Jaczewskiego 8 (SPSK Nr 4) tel.727920721 ewateresaguz@gmail.com Nalepa Dorota Wojewódzki Szpital Specjalistyczny Oddział Neurologii Al. Kraśnickie 100 20-718 Lublin tel. 668748836 Czekirda Marta Zakład Podstaw Pielęgniarstwa i Dydaktyki Medycznej 20-081 Lublin ul. S. Staszica 6 (Collegium Maximum) tel. +48 81448 6800 Brodowicz Magdalena Katedra i Zakład Pielęgniarstwa Pediatrycznego 20-093 Lublin ul. Antoniego Gębali 6 (USzD) +48 81718 5375 Streszczenie Cel pracy: Wykazanie na podstawie badań, braku rozwiązań logistycznych potrzebnych do wypełnienia funkcji edukacyjnej w oddziałach szpitalnych. Badania przeprowadzono w Szpitalu Powiatowym w Łęcznej w 2013 r. Wzięło w nich udział 100 osób chorujących na nadciśnienie tętnicze. Do badań wykorzystano kwestionariusz ankiety składający się z 36 pytań jako narzędzie badawcze. Głównym celem przeprowadzonych badań była ocena wiedzy chorych na temat nadciśnienia tętniczego i powikłań związanych z tą jednostką chorobową. Badania własne wykazały, że pacjenci mają niski poziom wiedzy na temat istoty choroby i czynników sprzyjających jej rozwojowi, co stanowi poważne zagrożenie dla ich zdrowia i życia. Taki stan sugeruje zaniedbania w edukacji chorych w oddziałach szpitalnych. Na potwierdzenie tego stanu rzeczy porównano badania własne z badaniami poziomu wiedzy rodziców dzieci z wadami serca, wadami genetycznymi oraz zespołem Dandy-Walkera. Porównanie pokazało identyczne braki wiedzy. Wyniki powyższych badań dają podstawę do poszukiwania nowych rozwiązań logistycznych w pracy pielęgniarek w celu wyeliminowania zaniedbań w sferze edukacji chorych i ich rodzin. Słowa kluczowe: pielęgniarstwo, edukacja, nadciśnienie tętnicze. Educational function in nursing – basis for seeking logistics solutions. Abstract Aim: To prove on the basis of research lack of logistics solutions required for fulfilling educational function in hospital wards. Research was conducted in the District Hospital in Łęczna in 2013. 100 persons with hypertension took part. The questionnaire consisting of 36 questions was used as a research tool. The main aim of the research was to assess sick persons’ knowledge about the hypertension and complications associated with this disease. Own studies showed that the patients have low level of knowledge about the essence of the disease and factors conductive to its development which constitutes to a serious threat to the patients’ health and life. Such state suggests negligence in education of sick persons in hospital wards. To confirm it, the comparison of own research with the studies of knowledge level of parents with children with heart defects, genetic defects and Dandy-Walker syndrome was made. The comparison showed identical lack of knowledge. The results of the research give the basis to seek for new logistics solutions in nurses’ work in order to eliminate negligence in the area of education of sick ones and their families. Key words: education, nursing, hypertension.